Lanthanum vanadate loaded carbon nitride Z-type heterojunction photocatalyst, photocatalytic film, preparation method and application
By supporting lanthanum vanadate on graphite carbon nitride, Z-type heterojunction photocatalyst is constructed, and the problem of low degradation efficiency of existing photocatalysts when treating PPCPs is solved, efficient and stable pollutant degradation is achieved, and good reusability is achieved.
Patent Information
- Application Number
- CN202411739362.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
Existing photocatalysts have limited degradation efficiency when dealing with drug and personal care product pollutants (PPCPs), and are inadequate in stability and reusability.
A Z-type heterojunction photocatalyst supported by lanthanum vanadate with graphite carbon nitride was prepared by high-temperature calcination-assisted deposition-precipitation method, and a photocatalytic film was prepared by casting method.
The degradation effect of PPCPs is significantly improved, and the photocatalytic film has good stability and reusability, and can effectively degrade organic pollutants in a water environment.
Smart Images

Figure CN119549180A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of synthesis of photocatalytic films, and more specifically, relates to a lanthanum vanadate-loaded carbon nitride Z-type heterojunction photocatalyst, a photocatalytic film, a preparation method and an application thereof. Background Art
[0002] In recent years, with the rapid development of economy and industry, the presence of refractory organic matter in water bodies has become an important problem of water pollution and water shortage. Pharmaceuticals and personal care products (PPCPs) are emerging pollutants. In recent years, with the widespread use of PPCPs in medical and daily life, their production and consumption have also increased. The current sewage treatment process mainly targets water quality indicators such as total nitrogen and total phosphorus, and there is less targeted treatment of PPCPs. Therefore, the tail water usually still contains low concentrations of PPCPs. PPCPs may cause antibiotic resistance, reproductive disorders, biomagnification, bioaccumulation and other problems. If they are not treated in a timely and effective manner, they will have adverse effects on humans and the environment. Therefore, it is of great significance to deeply treat the tail water and remove harmful PPCPs. Advanced oxidation technology (AOPs), as a new and efficient method that has attracted much attention in recent years, aims to remove organic pollutants, among which photocatalytic degradation of organic matter is one of the important research directions.
[0003] As a new type of metal-free and visible light-responsive semiconductor photocatalyst, g-C3N4 has a wide range of applications in the field of photocatalytic degradation of PPCPs, but its weak light absorption ability, low specific surface area, and high carrier recombination rate limit its development. LaVO4 is a visible light-responsive oxygen-containing salt photocatalyst. The presence of the 4f orbital structure of the lanthanum element in lanthanum vanadate (LaVO4) provides multiple possibilities for electron transitions, thereby showing efficient photocatalytic activity and having certain application potential in the field of pollutant degradation. However, due to the wide band gap of LaVO4, its response range to visible light is narrow, which limits its photocatalytic efficiency under visible light irradiation.
[0004] In order to improve the catalytic effect, after searching, patent CN113663705A discloses a lanthanum vanadate / graphite carbon nitride composite material and its preparation method, as well as its application as a photocatalyst. The preparation method of the invention includes: preparing graphite carbon nitride nanosheets and lanthanum vanadate nanosheets; mixing and grinding the lanthanum vanadate nanosheets and graphite carbon nitride and then calcining to obtain a lanthanum vanadate / graphite carbon nitride composite material. However, in the composite material, the lanthanum vanadate nanosheets are modified to the surface of the graphite carbon nitride under the action of intermolecular van der Waals forces, and the heterogeneous structure has limited efficiency in the degradation of PPCPs. Jing L et al. published in "Direct Z-scheme red carbon nitride / rod-like lanthanum vanadate composites with enhanced photodegradation of antibiotic contaminants" that a direct Z-scheme heterojunction photocatalyst based on red carbon nitride / rod-like LaVO4 was constructed by hydrothermal method. The composite material was made of red carbon nitride and rod-like lanthanum vanadate. Compared with ordinary light yellow carbon nitride, red carbon nitride has a wider light response range, but the preparation method of red carbon nitride is complicated and difficult to obtain. Therefore, it is urgent to prepare a photocatalyst suitable for PPCPs. Summary of the invention
[0005] 1. Problem to be solved
[0006] In view of the problem that the existing photocatalysts have limited efficiency in degrading PPCPs, the first object of the present invention is to provide a lanthanum vanadate-loaded carbon nitride Z-type heterojunction photocatalyst and a preparation method thereof, wherein the prepared photocatalyst effectively improves the degradation effect of PPCPs;
[0007] The second purpose of the present invention is to use the above-mentioned photocatalyst to prepare a photocatalytic film, and apply the photocatalytic film to an aqueous environment containing PPCPs. The photocatalytic film exhibits excellent degradation effect and has good stability and reusability.
[0008] 2. Technical solution
[0009] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0010] The first object of the present invention is to provide a photocatalyst, which includes g-C3N4 and LaVO4 loaded on the g-C3N4, wherein the g-C3N4 is a lamellar structure, the LaVO4 is granular, loaded on the surface of the g-C3N4 and in the folds between the lamellar layers, and a direct Z-type heterojunction is formed between the g-C3N4 and LaVO4.
[0011] In the photocatalyst, the g-C3N4 is graphite carbon nitride, and the LaVO4 is a monoclinic phase.
[0012] LaVO4 has two types of crystal structures, monoclinic phase (m-LaVO4) and tetragonal phase (t-LaVO4). 3+ With a larger radius, LaVO4 tends to form a monoclinic phase of lanthanum vanadate with a higher oxygen coordination number. The monoclinic phase of lanthanum vanadate has stronger catalytic activity. The reason is that (1) La 3+ and VO4 3- It has good charge distribution and can stimulate the physical and chemical properties of vanadium; (2) the monoclinic phase of lanthanum vanadate has a larger specific surface area than the tetragonal phase of lanthanum vanadate and has a higher light utilization efficiency; (3) the monoclinic phase of lanthanum vanadate has good crystallinity and a narrow bandgap, so that the transition of electrons from the valence band to the conduction band requires only a small amount of energy, making it easier to generate photogenerated electron-hole pairs and more responsive to visible light; (4) the band structure of the monoclinic phase of lanthanum vanadate is more compatible with the band structure of carbon nitride, among which the conduction band (CB) position of the monoclinic phase of lanthanum vanadate is relatively low, at -0.75 eV, while the valence band (VB) position is relatively high, at 1.75 eV, which helps to promote the transfer of photogenerated holes on the conduction band of carbon nitride to the valence band of lanthanum vanadate, forming a longer charge transfer path and improving the lifetime of photogenerated carriers.
[0013] Among them, the g-C3N4 is a lamellar carbon nitride obtained after hydrochloric acid peeling, and its surface presents a broken lamellar stacking structure, exposing the fold structure between the lamellar structures.
[0014] Furthermore, the size of the carbon nitride sheet g-C3N4 is 10-20 μm. LaVO4 is in granular form and loaded on the surface and in the pores of CNS, and the size of LaVO4 in the heterostructure is 20-40 nm.
[0015] Furthermore, the loading amount of LaVO4 in the photocatalyst is 2wt% to 10wt%, denoted as Xwt%LaV / CNS.
[0016] When the loading amount of LaVO4 is 4wt%, the band gap width of 4wt%LaV / CNS photocatalyst is 2.83eV, the VB position is 1.41eV, and the light absorption threshold is 370-600nm. After 5 cycles, 4wt%LaV / CNS still has an excellent LVX removal rate (94.9%). The leaching concentration of lanthanum ions and vanadium ions in the catalyst during the reaction is low, indicating that 4wt%LaV / CNS has good stability and reusability.
[0017] The method for preparing the above-mentioned photocatalyst comprises the steps of:
[0018] Step S1, preparation of g-C3N4 nanosheets: preparing carbon nitride nanosheets by thermal shrinkage polymerization and strong acid stripping, which specifically includes the following steps:
[0019] a. Weigh 5-15g of melamine, grind it thoroughly and put it into a crucible, wrap it with tin foil, place the crucible in a muffle furnace, heat it to 550-600℃ at 3-10℃ / min and calcine it for 4 to 6h; after the crucible is cooled naturally, take it out and grind the yellow solid into powder to obtain g-C3N4;
[0020] b. Take 1g g-C3N4 and 100ml 6M hydrochloric acid and place them in a 250ml polytetrafluoroethylene reactor. Hydrothermally react at 120℃~140℃ for 4~6h to obtain light yellow g-C3N4 nanosheets, which are recorded as CNS.
[0021] Step S2, preparation of LaVO4 / g-C3N4 photocatalyst: preparing the photocatalyst by high temperature calcination assisted deposition-precipitation method, the specific steps of which include:
[0022] a. Add 0.27234-1.36168g g-C3N4 into 20mL 25mM La(NO3)3·6H2O solution in proportion and stir for 30-60min;
[0023] b. Slowly drop NH4VO3 solution into the above suspension under continuous stirring, and adjust the pH to 7-7.5 with NH3·H2O. After ultrasonic treatment for 60-70 minutes, wash and filter with ultrapure water and anhydrous ethanol respectively, and dry at 60-80°C for 12-16 hours;
[0024] Furthermore, the molar ratio of La(NO3)3·6H2O and NH4VO3 is 1:3;
[0025] c. Take the dry powder obtained in step b, heat it at 220-250 ° C for 2-2.5 h in an inert atmosphere, wash it with ultrapure water and anhydrous ethanol, filter it, and dry it at 60-80 ° C for 12-16 h to obtain g-C3N4 / LaVO4 photocatalyst, named Xwt%LaV / CNS, where X wt% is the loading amount of LaVO4 in the photocatalyst, and the value of X is 2-10;
[0026] Furthermore, the heating rate is 3-5°C / min; the inert atmosphere is a nitrogen atmosphere, in addition to which, a helium atmosphere, an argon atmosphere, or a neon atmosphere may also be used.
[0027] Another object of the present invention is to provide a photocatalytic film, which includes a film carrier and a photocatalyst, wherein the active species are dispersed in the film carrier, and the photocatalyst includes g-C3N4 and LaVO4 loaded on the g-C3N4, wherein the g-C3N4 is a flaky structure, and the LaVO4 is granular and loaded on the surface of the g-C3N4 and in the folds between the lamellae, and a direct Z-type heterojunction is formed between the g-C3N4 and LaVO4.
[0028] Furthermore, the g-C3N4 is graphite carbon nitride, and the LaVO4 is a monoclinic phase.
[0029] The membrane carrier may be polyvinylidene fluoride. In addition, one or more of polyethylene terephthalate and polyether sulfone may also be selected.
[0030] Preferably, the loading amount of the photocatalyst in the photocatalytic film is 2 wt%-10 wt%.
[0031] The LaV / CNS photocatalytic film is prepared by a tape casting method. The method for preparing the above-mentioned photocatalytic film comprises the steps of:
[0032] Dissolve 6g PVDF powder in 120-160ml DMF, add 0.2-0.5g Xwt% LaV / CNS photocatalyst after PVDF is completely dissolved to make a uniform suspension, take 60-80ml of the suspension, spread it evenly on a 20cm×20cm glass plate, and dry it in a vacuum oven at 80℃-100℃ for 12-16h to obtain a LaV / CNS photocatalytic film, i.e., the photocatalytic film of the present application.
[0033] The present invention uses graphite carbon nitride as a carrier, loads lanthanum vanadate nanoparticles, and prepares a Z-type heterojunction photocatalytic film with lanthanum vanadate nanoparticles loaded on the surface of the flaky carbon nitride. In the preparation process, the present application uses a high-temperature calcination-assisted deposition-precipitation method to prepare a photocatalyst, and prepares a LaV / CNS photocatalytic film by a casting method. The prepared photocatalytic film has a high catalytic degradation effect, cycle stability, good hydrophilicity and recyclability.
[0034] The reasons why the photocatalytic film has a high catalytic degradation effect are: (1) LaVO4 affects the microscopic morphology of g-C3N4, so that the surface roughness of g-C3N4 increases, increasing the reaction active sites, which is more conducive to capturing trace pollutants in water, promoting photocatalytic reactions, and effectively degrading pollutants; (2) The prepared Xwt% LaV / CNS photocatalyst forms a 0D / 2D multi-level heterogeneous structure, which can cause the incident light to be refracted and reflected multiple times on the surface of the photocatalyst, thereby improving the light absorption capacity, having good light absorption capacity, low charge recombination rate, long carrier decay lifetime, and a long multi-step electron transfer path. The specific electron transfer path is: under light, the electrons in g-C3N4 and LaVO4 are excited to their respective CBs, leaving holes on VB, thereby generating photogenerated electron-hole pairs; among which the e on the LaVO4 CB - With h on g-C3N4 VB + recombination, while the e on g-C3N4 CB - Reacts with O2 to produce O2 - , h on LaVO4 VB + Will further oxidize O2 - , producing a part 1 O2, while the other part 1 O2 is activated by g-C3N4 through energy transfer under light. 1 O2. Therefore, the final formation is O2 - As the main active species, 1 O2 and H + The photocatalytic reaction system is jointly participated in and a Z-type heterostructure is formed, which effectively improves the separation efficiency of the photogenerated electron-hole pairs of the photocatalyst and the photocatalytic degradation efficiency; it has good ORR activity.
[0035] The reason why the photocatalytic film has excellent hydrophilicity is that the catalyst needs to have good hydrophilicity to increase the contact probability between the catalyst and the pollutant, thereby increasing the degradation rate of the pollutant. The contact angles of 4wt% LaV / CNS, LaVO4 and CNS are 22.9°, 17.4° and 57.2° respectively. The hydrophilicity of the three materials from strong to weak is LaVO4, 4wt% LaV / CNS, and CNS. After LaVO4 is compounded with CNS, LaVO4 significantly improves the hydrophilicity of CNS. On the one hand, this is because the more hydrophilic LaVO4 is loaded on the less hydrophilic CNS, which promotes the adsorption and diffusion of water molecules at the interface, and the interfacial interaction enhances the hydrophilicity of the composite material; on the other hand, the introduction of LaVO4 affects the electronic structure of CNS, especially the triazine ring structure. This structural adjustment changes the surface charge properties of the material, making the surface easier to interact with water molecules and enhancing the hydrophilicity. The carbon-nitrogen double bond in the polar chemical bond N=CN in the triazine ring structure has a higher electron density. This electron distribution characteristic can enhance the interaction between the material and water molecules, enhance the hydrophilicity of the material, and help improve the adsorption of water molecules on the surface of the material, thereby affecting the transfer and separation of charges, which is more conducive to promoting the catalytic degradation process.
[0036] The photocatalytic film is recyclable: after recycling, LaV / CNS still has an excellent antibiotic removal rate, and the leaching concentration of lanthanum ions and vanadium ions in the catalyst is low during the reaction. The catalyst can be almost completely decomposed at high temperature, which is conducive to the recycling of the used catalyst.
[0037] The present application constructs a Z-type heterojunction between graphite carbon nitride and lanthanum vanadate and uses it as the active material of the photocatalytic film, thereby improving the catalytic degradation effect while ensuring stability. The invention can be applied to the treatment of organic pollutants in the water environment and is beneficial to the recycling of the photocatalytic film.
[0038] 3. Beneficial effects
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The photocatalyst of the present invention includes g-C3N4 and LaVO4 loaded on the sheet structure g-C3N4, and a direct Z-type heterojunction is formed between g-C3N4 and LaVO4, which has more reactive active sites, effectively improves the degradation effect of the photocatalyst on PPCPs, and has good stability and reusability;
[0041] (2) The g-C3N4 used in the photocatalyst of the present invention is graphite carbon nitride, and LaVO4 is a monoclinic phase. The monoclinic phase of lanthanum vanadate has good crystallinity and a narrow bandgap width, and its band structure is more compatible with the band structure of carbon nitride. The position of the conduction band (CB) of the monoclinic phase of lanthanum vanadate is relatively low, while the position of the valence band (VB) is relatively high, which can better promote the transfer of photogenerated holes on the conduction band of carbon nitride to the valence band of lanthanum vanadate, forming a longer charge transfer path and improving the lifetime of photogenerated carriers; thereby improving the degradation effect of photocatalytic degradation of PPCPs;
[0042] (3) The photocatalyst of the present invention is compounded with CNS by LaVO4, and LaVO4 significantly improves the hydrophilicity of CNS, effectively improving the hydrophilicity of the catalyst, thereby being more conducive to promoting the catalytic degradation process;
[0043] (4) In the photocatalytic film of the present invention, LaV / CNS photocatalyst is added as an active component to improve the catalytic degradation effect while ensuring stability, which can be applied to the treatment of organic pollutants in water environment and is conducive to the recycling of photocatalytic film;
[0044] (5) Carbon nitride will spontaneously decompose at high temperatures, which is beneficial for post-use processing and is not prone to secondary pollution. 4wt% LaV / CNS does not undergo thermal decomposition below 338°C and has good thermal and oxidative stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments, but it should be understood that these drawings are designed only for explanation purposes and are not intended to limit the scope of the present invention. In addition, unless otherwise specified, these drawings are intended only to conceptually illustrate the structural configurations described herein and are not necessarily drawn to scale.
[0046] Figure 1 Microscopic morphology images of CNS (ac), LaVO4 (df) and 4wt% LaV / CNS (gi);
[0047] Figure 2 TEM images of 4wt% LaV / CNS heterostructure at 100nm (a) and 50nm (b) magnification fields, HR-TEM images (c) and EDS element mapping images (dh);
[0048] Figure 3 X-ray diffraction spectra of LaVO4, CNS and different LaV / CNS composites;
[0049] Figure 4 Fourier transform infrared spectra of LaVO4, CNS and different LaV / CNS composites;
[0050] Figure 5 High-resolution XPS spectra of 4wt% LaV / CNS, including the spectra of C1s (a, b), N1s (c, d), La3d (e, f) and V2p (g, h);
[0051] Figure 6 The XPS total spectrum of 4wt%LaV / CNS, CNS and LaVO4;
[0052] Figure 7 Nitrogen adsorption-desorption isotherms of 4wt% LaV / CNS, LaVO4 and CNS;
[0053] Figure 8 The contact angle diagram of 4wt%LaV / CNS, LaVO4 and CNS;
[0054] Fig. 9 Thermogravimetric spectra of 4wt% LaV / CNS in N2 and O2 atmospheres respectively;
[0055] Fig.10 UV-visible diffuse reflectance spectra (a) and band gap diagram (b) of LaVO4 and CNS at 4wt% LaV / CNS;
[0056] Fig.11 Photoluminescence spectra (a) and time-resolved photoluminescence spectra (b, c, d) of CNS, LaVO4 and 4wt% LaV / CNS under an excitation wavelength of 335nm;
[0057] Fig.12 X-ray photoelectron spectroscopy-valence band spectrum of 4wt%LaV / CNS, LaVO4 and CNS;
[0058] Fig.13 The D-band center position of 4wt%LaV / CNS, LaVO4 and CNS;
[0059] Fig.14 The photocatalytic degradation efficiency (a) and rate constant (b) of LVX by catalysts with different LaVO4 loadings;
[0060] Fig.15 The photocatalytic degradation efficiency (a) and rate constant (b) of LVX by different catalysts;
[0061] Fig.16 The stress-strain diagram and the maximum tensile stress (TensileStress), elastic modulus (Elastic Modulus) and tensile strain fracture value (Tensile Strain) of 4wt% LaV / CNS photocatalytic film;
[0062] Fig.17 This is the contact angle diagram of 4wt% LaV / CNS photocatalytic film;
[0063] Fig.18 This is the degradation curve of the photocatalytic device running continuously for 240 minutes. DETAILED DESCRIPTION
[0064] The following detailed description of exemplary embodiments of the present invention refers to the accompanying drawings, which form a part of the description, and in which exemplary embodiments of the present invention that can be implemented are shown as examples. Although these exemplary embodiments are described in sufficient detail to enable those skilled in the art to implement the present invention, it should be understood that other embodiments can be implemented and various changes can be made to the present invention without departing from the spirit and scope of the present invention. The following more detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but is only for the purpose of illustrating and not limiting the description of the characteristics and features of the present invention, so as to propose the best mode for performing the present invention and to enable those skilled in the art to implement the present invention. Therefore, the scope of the present invention is limited only by the appended claims.
[0065] Graphitic carbon nitride (g-C3N4) is a new type of semiconductor photocatalyst with unique properties and broad application prospects. The construction of heterojunction is a strategy to efficiently improve the photocatalytic performance. Two semiconductor materials with matching energy band structures are combined into a new composite photocatalytic material through a specific composite method. After the heterojunction is formed, at the interface between different semiconductor materials, there will be a flow of carrier materials at the interface. This flow not only optimizes the charge distribution at the interface, but also forms a built-in electric field at the interface, which can effectively drive the migration of photogenerated electrons and holes. Under illumination conditions, photogenerated electrons and holes migrate in the opposite direction under the action of the built-in electric field. This reverse migration effectively inhibits the recombination of photogenerated carriers. However, its defects such as weak light absorption ability, low specific surface area, and high carrier recombination rate limit its development.
[0066] LaVO4 is a visible light responsive oxygen-containing salt photocatalyst. The presence of the 4f orbital structure of the lanthanum element in lanthanum vanadate (LaVO4) provides multiple possibilities for electron transitions, thereby showing efficient photocatalytic activity and having certain application potential in the field of pollutant degradation. However, due to the wide band gap of LaVO4, its response range to visible light is narrow, which limits its photocatalytic efficiency under visible light irradiation. LaVO4 with different morphologies (sheet, rod, etc.) has different band structures (2.0-2.8 eV) and can form heterojunctions with different structures with g-C3N4 to improve photocatalytic activity. After being stripped by hydrochloric acid, g-C3N4 becomes CNS. The large amount of LaVO4 loaded on the surface of CNS significantly increases the roughness of its surface. The increased roughness of the LaV / CNS surface leads to more active sites on LaV / CNS, which is more conducive to the catalytic reaction.
[0067] Example 1
[0068] A photocatalyst in Example 1, wherein the mass fraction of LaVO4 in the photocatalyst is 4wt%.
[0069] Wherein, the preparation method of 4wt% LaV / CNS is:
[0070] Step S1, preparation of g-C3N4 nanosheets:
[0071] a. Weigh 10 g of melamine, grind it thoroughly and put it into a crucible, and wrap it with tin foil; place the crucible in a muffle furnace, heat it to 550 ° C at 5 ° C / min and calcine it at high temperature for 4 hours; after the crucible is cooled naturally, take it out, grind the yellow solid into powder to obtain g-C3N4;
[0072] b. Take 1g g-C3N4 and 100ml 6M hydrochloric acid and place them in a 250ml polytetrafluoroethylene reactor. Hydrothermally react at 120℃ for 4h to obtain light yellow g-C3N4 nanosheets, which are recorded as CNS.
[0073] Step S2, preparation of g-C3N4 / LaVO4 photocatalyst:
[0074] a. Add 0.54467 g g-C3N4 into 20 mL 25 mM La(NO3)3·6H2O solution and stir for 30 min;
[0075] b. 60 mL of 25 mM NH4VO3 solution was slowly added dropwise to the above suspension under continuous stirring, and the pH was adjusted to 7 with NH3·H2O. Ultrasonication was performed for 60 min, and the mixture was washed and filtered with ultrapure water and anhydrous ethanol respectively, and then dried at 60 ° C for 12 h;
[0076] c. Take the dry powder obtained in step b, heat it at 250°C for 2h at a heating rate of 5°C / min under a nitrogen atmosphere, wash and filter it with ultrapure water and anhydrous ethanol respectively, and then dry it at 60°C for 12h to obtain g-C3N4 / LaVO4 photocatalyst, recorded as 4wt% LaV / CNS.
[0077] Among them, the preparation process of pure LaVO4 nanoparticles is as follows: 25mM NH4VO3 solution is slowly added dropwise into 25mM La(NO3)3·6H2O solution under continuous stirring and stirred for 30 minutes, the pH is adjusted to 7 with NH3·H2O, ultrasonicated for 60 minutes, washed and filtered with ultrapure water and anhydrous ethanol respectively, and then dried at 60°C for 12 hours, the above-mentioned dried powder is taken, heated at 250°C for 2 hours at a heating rate of 5°C / min under a nitrogen atmosphere, and then washed and filtered with ultrapure water and anhydrous ethanol respectively, and then dried at 60°C for 12 hours to obtain LaVO4 nanoparticles.
[0078] Example 2
[0079] The preparation steps of the photocatalyst in Example 2 are the same as those in Example 1, except that the mass fraction of LaVO4 loading in the photocatalyst is 0 wt%, which is recorded as 0 wt% LaV / CNS.
[0080] Example 3
[0081] The preparation steps of the photocatalyst in Example 3 are the same as those in Example 1, except that the mass fraction of LaVO4 loading in the photocatalyst is 2 wt%, which is recorded as 2 wt% LaV / CNS.
[0082] Example 4
[0083] The preparation steps of the photocatalyst in Example 4 are the same as those in Example 1, except that the mass fraction of LaVO4 loading in the photocatalyst is 6 wt%, which is recorded as 6 wt% LaV / CNS.
[0084] Example 5
[0085] The steps of the photocatalyst in Example 5 are the same as those in Example 1, except that the mass fraction of LaVO4 loading in the photocatalyst is 8 wt%, which is recorded as 8 wt% LaV / CNS.
[0086] Example 6
[0087] The preparation steps of the photocatalyst in Example 6 are the same as those in Example 1, except that the mass fraction of LaVO4 loading in the photocatalyst is 10 wt%, denoted as 10 wt% LaV / CNS.
[0088] The experiment characterized the microscopic morphology of the photocatalyst by SEM, such as Figure 1 As shown in (ac), the g-C3N4 in the photocatalyst structure prepared in Example 1 becomes g-C3N4 nanosheets (CNS) after hydrochloric acid peeling, and its surface presents a broken sheet stacking structure, exposing the fold structure between the sheet structures. Figure 2 As shown in (c), after LaVO4 is loaded on CNS, LaVO4 is not easy to aggregate. LaVO4 is mainly in granular form and the loading position is mainly located on the surface of CNS and in the pores. The large amount of LaVO4 loaded on the surface of CNS significantly increases the roughness of its surface, making LaV / CNS have more active sites, which is more conducive to the catalytic reaction.
[0089] The crystal structure and phase composition of all samples were analyzed by XRD. Figure 3 As shown in the figure, the characteristic diffraction peak of CNS at 27.6° is attributed to the stacked conjugated aromatic structure (002), and the characteristic peaks of LaVO4 appear at 2θ of 23.9°, 26.2°, 27.6°, 29.8°, 32.4°, 34.8°, and 40.3°, which are respectively attributed to the characteristic diffraction peaks of (020), (200), (120), (012), (202), (212), and (221) of the crystal plane of the monoclinic phase LaVO4. The characteristic peaks of LaV / CNS with different ratios appearing at 2θ of 27.6° and 29.8° are analyzed, among which the characteristic peak at 27.6° corresponds to the conjugated aromatic structure (002) of CNS, and the weak characteristic peak at 29.8° corresponds to the (012) crystal plane of the monoclinic phase LaVO4. As the LaVO4 content increases, the conjugated aromatic structure in CNS reacts with LaVO4, and the conjugated aromatic structure signal of CNS gradually decreases. This may be due to the bonding reaction that occurs during the composite process of LaVO4 and CNS, which produces chemical bonds, destroys the conjugated aromatic structure, and provides more electron transfer paths.
[0090] like Figure 4 FT-IR spectra show that all samples have similar characteristic peaks, indicating that the introduction of LaVO4 has no significant effect on the structure of CNS, and the original structural characteristics of CNS are basically retained. -1 The characteristic peak at The spectrum of CNS is at 808cm -1 The characteristic peak at 900-1800cm is the characteristic absorption peak of the triazine ring. -1 The multiple peaks at 3000-3400cm are the stretching vibrations of CN and C=N heterocycles. -1The broad adsorption band at 808 cm indicates the stretching mode of -NH2 and NH groups and their intermolecular hydrogen bonding interactions. -1 The characteristic peak at is stronger than that of CNS, which confirms the presence of LaVO4 in the photocatalyst. After the composite of CNS and LaVO4, their respective structural characteristics are basically retained, and their original structural advantages are also retained, so that their microstructure can be better regulated and the photocatalytic performance can be improved.
[0091] like Figure 5 , 6 As shown in Figure 2, X-ray photoelectron spectroscopy is used to analyze the composition, chemical state, chemical structure, chemical bonding and other information on the sample surface. Figure 5 Compared with the N=CN binding energy of CNS in (b) (288.18 eV), Figure 5 The N=CN binding energy (288.16 eV) of 4wt% LaV / CNS in (a) is lower, which indicates that the introduction of LaVO4 into CNS affects the chemical environment of C in CNS, which mainly affects the structure of the triazine ring; similar to the C element, there is also the N element, which indicates that the introduction of LaVO4 mainly affects the triazine ring structure of CNS. Specifically, the reduction of the N=CN binding energy means that the electron transfer efficiency has been improved. The introduction of LaVO4 changes the distribution of electrons in CNS and promotes the transfer of electrons from CNS to LaVO4, thereby improving the electron transfer efficiency. Figure 3-5 In (ad), π→π* electron transfer occurs, which indicates that both 4wt% LaV / CNS and CNS are more easily excited by light. This enhanced light excitation ability helps to improve the separation efficiency of photogenerated carriers and has stronger catalytic activity. After compounding, the chemical environment of lanthanum changes, and there is a certain interaction between it and CNS. Figure 3-5In the V2p spectra of (g) and (h), the 516.63eV (V2p3 / 2) and 523.55eV (Vp1 / 2) spectra of vanadium show that the vanadium element is pentavalent in 4wt% LaV / CNS. In LaVO4, the 515.95eV (V2p3 / 2), 517.05eV (V2p3 / 2) and 523.39eV (V2p1 / 2), 524.83eV (V2p1 / 2) spectra of vanadium show that the vanadium element is tetravalent and pentavalent in LaVO4. This may be because during the heating process in a nitrogen atmosphere, due to the low content of LaVO4 in 4wt% LaV / CNS, the tetravalent vanadium is oxidized to a pentavalent state by the oxygen element in CNS, and LaVO4 has no other oxygen source in a nitrogen atmosphere, so the valence state of the vanadium element cannot be changed. This change in valence state helps to improve the activation ability of the photocatalyst for oxygen and water molecules, thereby generating more active oxygen species during the photocatalytic process. The above results all illustrate the good combination of CNS and LaVO4.
[0092] The specific surface area (SBET) of the photocatalyst can be obtained by measuring the nitrogen (N2) adsorption-desorption isotherm of the catalyst. In this experiment, high-purity N2 and helium (He) were used as adsorbent and carrier gas, respectively, and the specific surface area of 4wt% LaV / CNS, LaVO4 and CNS was tested. Figure 7 As shown in the figure, all samples conform to the IV type isotherm curve and have an H3 type hysteresis loop in the high pressure range (P / P0), indicating the existence of mesoporous structures in the three materials, and all of them are slit-shaped holes, which may come from the stacking of CNS. The specific surface areas (SBET) of 4wt% LaV / CNS, LaVO4 and CNS are 10.97m 2 / g,75.05m 2 / g and 20.36m 2 / g, compared with CNS and LaVO4, 4wt%LaV / CNS has a lower specific surface area because LaVO4 is deposited on CNS, which leads to the coverage of some pore structures on the surface of CNS.
[0093] In order to better treat pollutants in water, the photocatalyst needs to have good hydrophilicity to increase the contact probability between the catalyst and the pollutants, thereby increasing the degradation rate of the pollutants. Therefore, the contact angles of 4wt% LaV / CNS, LaVO4 and CNS were measured at room temperature, such as Figure 8As shown. The contact angles of 4wt% LaV / CNS, LaVO4 and CNS are 22.9°, 17.4° and 57.2° respectively. The hydrophilicity of the three materials is from strong to weak: LaVO4, 4wt% LaV / CNS, CNS. After LaVO4 is compounded with CNS, LaVO4 significantly improves the hydrophilicity of CNS, which is more conducive to promoting the catalytic degradation process.
[0094] Thermogravimetric analysis was used to test the thermal stability and oxidation stability of 4wt% LaV / CNS, providing a reference for the preparation and recycling of materials. The mass change curves of 4wt% LaV / CNS in N2 and O2 atmospheres are shown in Figure 2. Fig. 9 As shown, under the two atmospheres, 5.1% and 3.9% mass losses were observed when heated to 150°C, respectively, which was mainly due to the evaporation of water molecules adsorbed by the photocatalyst and its internal crystal water. Among them, under O2 atmosphere, the mass of the material dropped from 94.08% to 2.55% between 338°C and 565°C, which may be due to the destruction of oxygen-containing and nitrogen-containing functional groups of g-C3N4 to generate gases such as ammonia, carbon monoxide, and carbon dioxide, which stabilized between 565°C and 800°C. Under N2 atmosphere, a sharp mass loss occurred from 448°C to 702°C, and the mass dropped from 94.32% to 6.00%, and stabilized between 702°C and 800°C, which shows that carbon nitride will spontaneously decompose at high temperatures. In O2 atmosphere and N2 atmosphere, the residual mass at 800°C is 2.76% and 5.30% respectively. 4wt% LaV / CNS leaves only a very small amount of residue at high temperature, which is conducive to the treatment after actual use and is not prone to secondary pollution and other problems.
[0095] The energy band structure of the photocatalyst was studied by UV-Vis diffuse reflectance spectroscopy. UV-Vis diffuse reflectance spectroscopy was performed on 4wt% LaV / CNS, LaVO4 and CNS. Fig.10 As shown, the light absorption threshold of CNS and 4wt% LaV / CNS is 370-600nm, and the light absorption threshold of LaVO4 is 266-650nm. The light absorption capacity of CNS is enhanced after LaVO4 is compounded with CNS. The material band gap energy (Eg) is calculated by Kubelka-Munk formula to obtain the band gap of LaVO4 to be 3.16eV, the band gap of CNS to be 2.93eV, and the band gap of 4wt% LaV / CNS to be 2.83eV. The introduction of LaVO4 improves the light absorption capacity of CNS, which may be due to the formation of a 0D / 2D multi-level heterostructure between LaVO4 and CNS. The multi-level structure can cause the incident light to be refracted and reflected multiple times on the surface of the photocatalyst, thereby improving the light absorption capacity.
[0096] In order to investigate the behavior of photogenerated electron-hole separation, the photocatalysts were analyzed by photoluminescence spectroscopy (PL). Fig.11 As shown in (a), under the condition of excitation wavelength of 335nm, the emission peak of the sample is mainly concentrated around 465nm. The PL intensity of CNS is high, indicating that its charge recombination rate is high. After LaVO4 is compounded with CNS, the PL intensity of 4wt% LaV / CNS decreases significantly, indicating that its charge recombination rate decreases, which helps to promote charge transfer, thereby reducing the probability of electron and hole recombination. Fig.11 As shown in (b)-(d), the average carrier lifetime of LaVO4 is 4.47ns, the average carrier lifetime of CNS is 5.41ns, and the average carrier lifetime of 4wt%LaV / CNS is 5.34ns. The average carrier lifetimes of CNS and 4wt%LaV / CNS are significantly longer than those of LaVO4. Fig.11 The PL peak intensity of various samples in (a) shows that the recombination of LaVO4 and CNS significantly reduces the charge recombination rate of CNS, and due to the long-distance multi-step charge transfer path induced by the heterostructure, the photogenerated carriers of 4wt% LaV / CNS have a longer decay lifetime.
[0097] The valence band (VB) of the catalyst was obtained by X-ray photoelectron spectroscopy-valence band spectroscopy (VB-XPS), such as Fig.12 As shown. According to the research results, the VB position of LaVO4 is 2.24eV, the VB position of CNS is 1.75eV, and the VB position of 4wt%LaV / CNS is 1.41eV. The upward shift of the conduction band position is conducive to the generation of substances with higher reduction potentials, which helps to improve the photocatalytic activity of the photocatalyst. It is calculated that the CB edge of LaVO4 is -0.75eV, the CB edge of CNS is -1.18eV, and the CB edge of 4wt%LaV / CNS is -1.42eV. The more negative the conduction band position is, the stronger its reducing ability is, which is conducive to the transfer of electrons and the reduction reaction. The center position of the D band of LaVO4 is -5.49eV, the center position of the D band of CNS is -5.15eV, and the center position of the D band of 4wt%LaV / CNS is -4.99eV. As shown Fig.13 As shown in the figure, the D band center position of 4wt% LaV / CNS has shifted upward relative to LaVO4 and CNS. The upward shift of the D band center position means that the Fermi level of the material moves upward, enhancing the electron acceptance ability of the photocatalyst, indicating that the composite of LaVO4 and CNS can improve the redox reaction activity. The active species in the LaV / CNS photocatalytic reaction is ·O2 - ,h + , 1 O2, of which O2 - is the main active species, followed by h + and1 O2, the electrons in the conduction band can be oxidized to ·OH, while the holes in the valence band can directly oxidize organic matter or react with water to generate ·OH.
[0098] Example 7
[0099] The 4wt% LaV / CNS photocatalyst prepared in Example 1 was applied to the degradation experiment of levofloxacin (LVX) to evaluate the influence of the preparation conditions on the catalyst performance. The reaction conditions met the following requirements: catalyst concentration 0.05g / L, levofloxacin (LVX) concentration = 20μg / L, initial pH = 7, light source: 350W xenon lamp, temperature 25°C.
[0100] Firstly, the effect of calcination temperature on 4wt% LaV / CNS during catalyst preparation was studied, and the temperature gradient was set at 200℃, 250℃, 300℃, and 350℃. The experimental results are shown in Fig.14 As shown in (a) and (b), all catalysts can completely degrade LVX within 60 minutes. At temperatures of 250°C, 300°C and 350°C, the catalysts can completely degrade LVX within 20 minutes. Among them, at 200°C, 4wt% LaV / CNS has the worst photocatalytic degradation effect of LVX, with the lowest reaction rate of 0.0591min. -1 When the temperature rises to 300℃, the effect of the catalyst on the degradation of LVX gradually increases, and the reaction rate increases to 0.2019min -1 When the temperature reaches 350℃, the effect of the catalyst on LVX degradation decreases, and the reaction rate decreases to 0.1612min -1 The study showed that when the temperature is between 200 and 300 °C, it is beneficial for LaVO4 to transform into monoclinic LaVO4, thereby improving the photocatalytic degradation performance. When the temperature is 250 °C and 300 °C, the degradation rates are similar, which are 0.1959 min and 0.223 min, respectively. -1 and 0.2019min -1 , from the perspective of cost and quality loss, 250℃ was adopted as the high temperature calcination temperature.
[0101] Effects of preparation processes with different LaVO4 loadings on photocatalytic degradation of LVX Fig.15 As shown. This embodiment sets the LaVO4 loading amount to 0wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt% mass fraction gradient. The experimental results show that when the LaVO4 loading amount is 4wt%, the rate of catalyst degradation of LVX is the largest (0.1959min -1). When the loading amount of LaVO4 is lower than 4wt%, the degradation rate of the catalyst decreases significantly. This may be because too little LaVO4 combines with CNS, and there is not enough charge transfer path, resulting in a high charge recombination rate, thereby reducing the activity of the catalyst. When the loading amount of LaVO4 is higher than 4wt%, the degradation rate of the catalyst decreases to a certain extent. This may be because LaVO4 will generate a large number of carriers under the excitation of simulated sunlight, resulting in a shortened carrier lifetime, thereby reducing the photocatalytic degradation performance; at the same time, a large amount of LaVO4 is prone to cause clustering, which weakens the activity of the catalyst.
[0102] Example 8
[0103] Example 8 is a LaV / CNS photocatalytic film, and the specific preparation method includes the following steps:
[0104] Dissolve 6 g of PVDF powder in 120 ml of DMF. After PVDF is completely dissolved, add 0.2 g of 4 wt% LaV / CNS photocatalyst prepared in Example 1 to make a uniform suspension. Take 60 ml of the suspension and spread it evenly on a 20 cm × 20 cm glass plate. After drying in a vacuum oven at 80°C for 12 h, a LaV / CNS photocatalytic film is obtained.
[0105] Through the membrane immobilization method, the material was used in actual scenarios, and the mechanical properties and hydrophilicity of the LaV / CNS photocatalytic membrane were analyzed to study its application feasibility. Fig.16 As shown, the experimental results show that the maximum tensile stress of the composite photocatalytic film is 28.06MPa, the elastic modulus is 441.12MPa, and the tensile strain fracture value is 52.62%, which indicates that the LaV / CNS photocatalytic film has strong toughness, is not easy to break, has excellent mechanical strength, and has practical application potential.
[0106] Because the reaction system is carried out under water medium conditions, the LaV / CNS photocatalytic film needs good hydrophilicity in the actual operation process to facilitate the reaction process. Good hydrophilicity is conducive to the formation of a thin liquid film on the surface of the film, which can provide good conditions for the reaction. Fig.17 The figure shows the contact angle of the 4wt% LaV / CNS photocatalytic film, and the contact angle is 81.4° (<90°). Therefore, the 4wt% LaV / CNS photocatalytic film has good hydrophilicity, which is beneficial to the reaction process.
[0107] The degradation experiment was set up with 20μg / L LVX as the target pollutant, the peristaltic pump flow rate was set to 20mL / min, and the total treatment volume was 15000mL. The reaction conditions were: LVX = 20μg / L, initial pH = 7, light source: 48W LED UV lamp, temperature 25℃, treatment volume: 15L.
[0108] In this embodiment, considering the practical application, the ultraviolet lamp is safer and has stronger energy. Fig.18 As shown in the figure, the degradation rate of LVX in the LaV / CNS photocatalytic film reached 83.5% within 240 minutes, while the degradation rate of LVX in the blank group without the addition of the photocatalytic film was 66.2% within 240 minutes. The experimental results show that the use of the LaV / CNS photocatalytic film effectively improves the degradation efficiency of LVX and maintains a high degradation rate within 240 minutes.
[0109] Example 9
[0110] Example 9 is a LaV / CNS photocatalytic film, and its preparation method is the same as that of Example 8.
[0111] The degradation experiment was set up with 20 μg / L LVX as the target pollutant, the peristaltic pump flow rate was set to 20 mL / min, and the total treatment volume was 15000 mL. The reaction conditions were: LVX = 20 μg / L, initial pH = 7, light source: 350W xenon lamp, temperature 25°C, treatment volume: 15L.
[0112] The LaV / CNS photocatalytic film also showed a high degradation efficiency for LVX under visible light conditions and maintained a high degradation rate within 240 minutes.
[0113] It can be seen that the LaV / CNS photocatalytic film is applicable to visible light and ultraviolet light conditions and has a wide light response range.
[0114] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.
Claims
1. A photocatalyst comprising g-C3N4 and LaVO4 loaded on g-C3N4, characterized in that: The g-C3N4 is a sheet structure, and the LaVO4 is granular and loaded on the surface of the g-C3N4 and in the folds between the sheets, and a direct Z-type heterojunction is formed between the g-C3N4 and LaVO4.
2. The photocatalyst according to claim 1, characterized in that The g-C3N4 is graphite carbon nitride, and the LaVO4 is a monoclinic phase.
3. The photocatalytic film according to claim 2, characterized in that: The loading amount of LaVO4 in the photocatalyst is 2wt% to 10wt%.
4. The photocatalyst according to claim 3, characterized in that The loading amount of LaVO4 on g-C3N4 is 4wt%, recorded as 4wt%LaV / CNS, and the band gap width of 4wt%LaV / CNS is 2.83eV, wherein the VB position is 1.41eV, and the CB position is -1.42eV.
5. The photocatalyst according to claim 4, characterized in that The contact angle of the 4wt% g-C3N4 / LaVO4 is 22.9°.
6. The photocatalyst according to claim 1, characterized in that The size of the g-C3N4 is 10-20 μm, the particle size of the LaVO4 is 20-40 nm, and the size of the g-C3N4 / LaVO4 is 10-20 μm.
7. A method for preparing the photocatalyst according to any one of claims 1 to 6, characterized in that: Includes steps: Step S1, preparation of g-C3N4 nanosheets: a. Calcine melamine at 550-600℃ for 4-6h and obtain g-C3N4 after cooling; b. hydrothermally reacting g-C3N4 with hydrochloric acid at 120°C-140°C for 4-6h to obtain g-C3N4 nanosheets; Step S2: Preparation of g-C3N4 / LaVO4 composite material: a. Take g-C3N4 and add it to La(NO3)3·6H2O solution and mix well; b. Slowly add NH4VO3 solution under continuous stirring, adjust pH to 7-7.5, ultrasonically react for 60-70 minutes, wash, filter and dry; c. Take the dry powder obtained in step b, heat it at 220-250°C for 2-2.5h in an inert atmosphere, wash, filter and dry to obtain g-C3N4 / LaVO4 photocatalyst, denoted as Xwt%LaV / CNS, where X wt% is the loading amount of LaVO4 in the photocatalyst.
8. A photocatalytic film, comprising a film carrier and an active species, wherein the active species is dispersed in the film carrier, the active species is the photocatalyst as described in any one of claims 1 to 6, the photocatalyst comprises g-C3N4 and LaVO4 loaded on the g-C3N4, the g-C3N4 is a sheet structure, the LaVO4 is granular, loaded on the surface of the g-C3N4 and in the folds between the sheets, and a direct Z-type heterojunction is formed between the g-C3N4 and LaVO4.
9. A method for preparing the photocatalytic film according to any one of claims 7 to 8, characterized in that: The method comprises the following steps: dissolving 6g of membrane carrier raw material in 120-160ml of DMF, adding 0.2-0.5g of Xwt% LaV / CNS photocatalyst after PVDF is completely dissolved to prepare a uniform suspension, taking 60-80ml of the suspension, spreading it evenly on a glass plate, and vacuum drying to obtain a LaV / CNS photocatalytic membrane.
10. Use of the photocatalytic film according to any one of claims 8 to 9, characterized in that: The photocatalytic film is applied to the photocatalytic degradation system of antibiotics.
Citation Information
Patent Citations
Lanthanum vanadate / graphite phase carbon nitride composite material as well as preparation method and application thereof
CN113663705A